Nas tramas da produção artesanal: narradoras de saberes cotidianos em Carmo do Rio Claro/MG - Natalia Achcar Monteiro Silva (2021)
The present study rescues the handicraft practices - hand weaving and embroidered fruit candy and jam - from Carmo do Rio Claro/MG, a small town in demographic terms, where urban and rural life are outlined in a subtle and fluid way. This knowledge, arising from traditional ways of doing things and considered intangible heritage in the municipality, has been transformed over time, especially when these things become economic activities, however, they are in danger of disappearing due to a series of issues. These issues range from the lack of incentives from the public authorities for the continuation of these practices, safeguarding the craftsman as a professional, and in this sense, there is a risk of erasing their own tradition and local identity, and even the absence of popular business management techniques, the weakening of the Association of Craftsmen with its cooperative system and the barely productive and often conflicting relationships with specialists, especially in fashion and interior design. Therefore, initially using the ethnographic method, and later effectively using oral memory, the proposal is built through my performance as a researcher and a “native” of this place, inhabiting the frontier where the stories and experiences of some artisans are recorded. Thus, assuming the female role and involving other potential agents in the discussion, some possible paths were thought out collectively. One such path was the creation of a Living Museum, which encompasses a building and goes beyond the scale of the city, thereby promoting more effective interactions and invigorated practices in the territory itself. Another path was a Free Craft School in which it is possible, in addition to teaching techniques, to manage production. Both aim at safeguarding traditions, revaluing knowledge on a local scale and leveraging on other scales, in addition to getting closer to the scientific fields of arts and design, in order to establish relational productions.